Altered brain cannabinoid 1 receptor mRNA expression across postnatal development in the MAM model of schizophrenia - Gomes, Felipe V. (Schizophr Res, 2018)
Altered cannabinoid 1 receptor (CB1R) expression has been reported in the brain of subjects with schizophrenia, a developmental mental illness that usually emerges in late adolescence/early adulthood. However, the developmental period at which changes in the CB1R expression appear in schizophrenia is unknown. To gain insight into this factor, we assessed the postnatal developmental trajectory of CB1R expression in the methylazoxymethanol (MAM) model of schizophrenia. Using in situ hybridization with film and grain analyses, CB1R messenger RNA (mRNA) levels were quantified in multiple brain regions, including the medial prefrontal cortex (mPFC), secondary motor cortex, dorsomedial and dorsolateral striatum, dorsal subregions and ventral subiculum of the hippocampus, of MAM-treated rats and normal controls at three developmental periods [juvenile - postnatal day (PD) 30; adolescence - PD45; and adulthood - PD85]. In all brain regions studied, CB1R mRNA levels were highest in juveniles and then decreased progressively toward adolescent and adult levels in control and MAM-treated rats. However, in MAM-treated rats, CB1R mRNA levels were lower in the mPFC at PD85 and higher in the dorsolateral striatum at PD45 and PD85 relative to controls. Cellular analyses confirmed the changes in CB1R mRNA expression in MAM-treated rats. These findings are in accordance with previous studies showing a decrease in the CB1R mRNA expression from juvenile period to adolescence to adulthood in cortical, striatal, and hippocampal regions. Additionally, similar to most of the schizophrenia-like signs observed in the MAM model, embryonic exposure to MAM leads to schizophrenia-related changes in CB1R mRNA expression that only emerge later in development.